Problematika Akhlak Peserta Didik dalam Mengikuti Proses Pembelajaran Pendidikan Agama Islam - Emi, Yulia; Oktaviani, Heriyah (Universitas Pahlawan Tuanku Tambusai, 2024)
The morals of students can be influenced by the surrounding environment. Local culture can also play an important role in shaping children's behavior and morals. Because a person's morals can be influenced by local cultural, environmental, and educational factors. It is important to understand and appreciate this diversity in an effort to improve character education throughout the region. In some areas such as the Pagar Alam area as we know the people in this area are very known for their friendliness even though the tone of speech in the Sumatra area is known for a speech style that sounds harsh if heard by others but in fact it is not. The purpose of this study is to know the moral problems of students when participating in the learning process and to know solutions in overcoming the moral problems of students in following the learning process of Islamic Religious Education. This kind of research. Qualitative research The approach used by researchers is a qualitative descriptive approach Data collection techniques used and to support the author's research data using interview guidelines, observation guidelines and documentation. There are students who do not want to be reprimanded or given directions, so the teacher will not force the child but the teacher there will still do or give punishment if the student violates the rules.